El hogar y el mundo. La imaginación en los discursos informativos y publicitarios. - Peñamarín, Cristina (CIC. Cuadernos de Información y Comunicación, 2007)
The article studies how the informative and advertising discourses build images of the world and of the subject, in particular in television. The flowing variety of the advertising spaces locates the home of the identity in the unconscious memory of its addressee and in his/her potentialities. The information, on the contrary, is presented always in the same frame, the invariable format of the informative discourse and the stable, reassuring, space-time of the study, from where it gives a local vision of the world and it reaffirms the addressee’s belonging to a collective identity and to a specific locality.